How to operate the duty free business in future? Is there a strategic logic of an airport-owned retail model? And if so, is this contradicted by cultural realities at Fraport? - Kreutel, Felix (2006)
The dissertation evaluates whether there is a necessity and possibility for Fraport, operator of Frankfurt Airport, to apply a different approach to operate its duty free business, in order to improve the performance of this very important revenue stream. Due to a changing industry context, airports have to rethink the role of airport retailing within their organisation and, in particular, have to thoroughly scrutinise their approach to operating the duty free business. With respect to this, the view of international airport retail experts constitutes the basis for identifying the required resources, for assessing retailing as a core competence and for evaluating the consequences for the operation model that is applied to manage the duty free business. The author suggests that there is a mutual causal relation between airport's development of retail competence and the self-operation model of the duty free business. Whether such an approach is successful or not, significantly depends on the organisation's resource base, its reason to be and its cultural reality. Therefore, in seeking to reach a comprehensive notion of the strategic decision - how to operate the duty free business - the dissertation investigates the influence of the airport's reason to be and Fraport's cultural reality. Finally, it draws a conclusion with regard to whether there is a strategic logic for an airport-owned retail model and whether this is in harmony with the cultural reality at Fraport.